2021
DOI: 10.1101/2021.10.30.466631
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Wildlife is imperiled in peri-urban landscapes: threats to arboreal mammals

Abstract: Urbanization and deforestation impose severe challenges to wildlife, particularly for forest-living vertebrates. Understanding how the peri-urban matrix impacts their survival is critical for designing strategies to promote their conservation. We investigated the threats faced by brown howler monkeys (Alouatta guariba clamitans) in peri-urban regions of Rio Grande do Sul (RS) and Santa Catarina (SC) states, southern Brazil, by compiling conflicts reported over more than two decades. We assessed the major confl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Management actions are being studied and implemented in several locations where primate populations are at risk in peri-urban zones. Some examples that can also be implemented in EERP are: the allocation of corridors, aerial bridges (Donaldson and Cunneyworth, 2015;Lindshield, 2016; NGO Kids Saving the Rainforest), and speed reducers to mitigate roadkill (Chaves et al, 2022); use of insulated cables to prevent electrocution (Chaves et al, 2022;Lindshield, 2016;Lokschin et al, 2007;Printes et al, 2010); sterilization of domestic and stray dogs to diminish their number and prevent attacks (Chaves et al, 2022;Lindshield, 2016;Oliveira et al, 2008) and environmental education and use of signs in sites where citizens are used to feeding the monkeys in order to discourage food supplementation in the long term, to keep the primates as wild as possible (Maibeche et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Management actions are being studied and implemented in several locations where primate populations are at risk in peri-urban zones. Some examples that can also be implemented in EERP are: the allocation of corridors, aerial bridges (Donaldson and Cunneyworth, 2015;Lindshield, 2016; NGO Kids Saving the Rainforest), and speed reducers to mitigate roadkill (Chaves et al, 2022); use of insulated cables to prevent electrocution (Chaves et al, 2022;Lindshield, 2016;Lokschin et al, 2007;Printes et al, 2010); sterilization of domestic and stray dogs to diminish their number and prevent attacks (Chaves et al, 2022;Lindshield, 2016;Oliveira et al, 2008) and environmental education and use of signs in sites where citizens are used to feeding the monkeys in order to discourage food supplementation in the long term, to keep the primates as wild as possible (Maibeche et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Further urbanization of EERP surroundings will probably increase threats faced by Sapajus nigritus population and then increase its mortality. A possible scenario may be similar to those of Alouatta guariba clamitans in urbanized areas in southern Brazil, where a long-term study suggested the main threats faced by these populations are electrocution, mistreatment, dog attacks, and roadkill (Chaves et al, 2022). So, we modeled the viability with a 2,5%, 5%, and 10% increase in mortality at all ages and sexes, except 0-1 year.…”
Section: Other Urban Threats Scenariomentioning
confidence: 98%
See 1 more Smart Citation